THE INFLUENCE OF THE ORGANIZATIONAL IN THE PROCESS OF KNOWLEDGE MANAGEMENT - Barbosa, Everaldo Henrique dos Santos [UNESP]; Moraes, Cássia Regina Bassan de [UNESP] (My University, 2022)
Organizational behavior is directly related to the professionals' actions in the work environment and influences the development aspects of the organization. Care in promoting organizational value culture is an explicit feature of organizational behavior and directly reflects management. Managers may not understand the relevance of aspects of organizational behavior. In this way, the research problem was designed to unveil and highlight how the valuation of organizational behavior can contribute to the development of the knowledge management process. The general objective was to investigate the relevant aspects of organizational behavior and its characteristics for the process of knowledge management within organizations. The methodology of the study approached a bibliographical research based on descriptive and exploratory descriptions of a qualitative nature to identify the concepts about organizational culture, organizational behavior and knowledge management in organizations. The results showed that Knowledge Management is an ability of the professional manager that not only depends on his / her competencies, but also on the whole organizational set, considering the culture of each professional that, in turn, directly influences the organizational behavior, generating different results according to the placement and organizational culture built in each organization.
A INFLUÊNCIA DO COMPORTAMENTO ORGANIZACIONAL NO PROCESSO DE GESTÃO DO CONHECIMENTO
Keywords: Knowledge management; Organizational behavior; Organizational culture; Organizations